Discussion of the properties of the accretion disk in a binary system based on the results of SPH-modeling - Agisheva А.А.; Khokhlov СА.; Agishev А.Т. (Recent Contributions to Physics, 2025)
When studying close binary systems (CBS), it is extremely important to study the complex dynamic structure of matter transfer during a computational experiment for the correct interpretation of observational data and determination of the evolutionary status of the star. In this paper, the accretion processes of the cataclysmic variable EZ Lyn (SDSS J080434.20+510349.2) are simulated using the SPH (smoothed particle hydrodynamics) method based on the available observational data. Hydrodynamic flows in the gravitational field of the white and brown dwarfs that form the specified compact binary system at the stage of late evolution are simulated. The coordinates (x, y, z), velocity components (v_x, v_y,v_z), mass, density, heat capacity, pressure, temperature, total energy and entropy of the "particles" specified by the set of initial parameters are calculated. Visual representations of the calculated values are obtained and analyzed. Periodic spirals due to disk precession and "arms" resulting from the resonance of orbital periods (2:1) and the transfer of excess angular momentum of the disk in the steady state were detected. Low temperatures of the accretion disk cause absorption of radiation, mainly during absorption on hydrogen and in ionization processes. Similar with analysis of the results of visualization of the density and temperatures observed in the studied system, fluctuations in the values of velocities, heat capacity, pressure, total energy and entropy were considered, and descriptions and possible mechanisms of the observed processes were given. Visualization is presented in 2-D and 3-D format. The results of the modeling coincide with observations confirming the asynchronous rotation of the components of a close binary system and the possibility of a resonance of their orbital periods. The applied SPH-method of modeling allows to present a physical model of an astrophysical phenomenon. In this case, a model of an accretion disk and processes of matter flow between components of a close binary system for subsequent description and analysis.